Developing Emotional Intelligence as a Key to Academic Success among High School Students - Gusma Afriani; Nurul Zaman (Civiliza Publishing, Indonesia., 2025)
This study explores the development of emotional intelligence as a key factor influencing academic success among high school students. The research was driven by the growing concern that Indonesia’s education system remains heavily focused on cognitive achievement while overlooking emotional and social competencies essential for holistic learning. The study aimed to examine how emotional intelligence contributes to academic success and to identify effective strategies for fostering it within school environments. Employing a qualitative descriptive design, the research was conducted at a public high school in West Java, Indonesia, using semi-structured interviews, classroom observations, and document analysis. The findings reveal that students with high levels of self-awareness, self-regulation, motivation, empathy, and social skills demonstrate greater learning persistence, intrinsic motivation, and collaboration, leading to improved academic outcomes. Moreover, emotionally supportive teachers and positive school culture significantly enhance students’ emotional growth and engagement. The study concludes that emotional intelligence is not a peripheral attribute but a central determinant of academic success and personal development. It recommends integrating socio-emotional learning into high school curricula to build resilient, empathetic, and self-motivated learners. The contribution of this research lies in its contextual insight into emotional intelligence development within the Indonesian educational framework.